ON THE MODERN INTERPRETATION OF THE HISTORY OF CHEMISTRY (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article provides statements on the harmonization of historical aspects and modern views on the discoveries, achievements, theories and laws of the great chemists who have made an undeniable contribution to the development of chemistry in teaching pupils and students